Laparoscopic versus open colorectal surgery in the acute setting (LaCeS trial): a multicentre randomized feasibility trial. Issue 12 (23rd June 2020) - Harji, D P; Marshall, H; Gordon, K; Twiddy, M; Pullan, A; Meads, D; Croft, J; Burke, D; Griffiths, B; Verjee, A; Sagar, P; Stocken, D; et al.
Abstract: Background: Approximately 30 000 people undergo major emergency abdominal gastrointestinal surgery annually, and 36 per cent of these procedures (around 10 800) are carried out for emergency colorectal pathology. Some 14 per cent of all patients requiring emergency surgery have a laparoscopic procedure. The aims of the LaCeS (laparoscopic versus open colorectal surgery in the acute setting) feasibility trial were to assess the feasibility, safety and acceptability of performing a large-scale definitive phase III RCT, with a comparison of emergency laparoscopic versus open surgery for acute colorectal pathology. Methods: LaCeS was designed as a prospective, multicentre, single-blind, parallel-group, pragmatic feasibility RCT with an integrated qualitative study. Randomization was undertaken centrally, with patients randomized on a 1 : 1 basis between laparoscopic or open surgery. Results: A total of 64 patients were recruited across five centres. The overall mean steady-state recruitment rate was 1·2 patients per month per site. Baseline compliance for clinical and health-related quality-of-life data was 99·8 and 93·8 per cent respectively. The conversion rate from laparoscopic to open surgery was 39 (95 per cent c.i. 23 to 58) per cent. The 30-day postoperative complication rate was 27 (13 to 46) per cent in the laparoscopic arm and 42 (25 to 61) per cent in the open arm. Conclusion: Laparoscopic emergency colorectal surgery may have an acceptable safety profile. Registration number: ISRCTN15681041 (http://www.controlled-trials.com ). Graphical Abstract: The LaCeS feasibility trial has demonstrated that it is possible to evaluate laparoscopic surgery in the emergency colorectal setting within the context of an RCT. It has also shown that it is possible to recruit to a surgical trial in the emergency setting, with good compliance to trial procedures and processes, and overall acceptability by patients and clinicians. Nicely tied LaCeS